Recurrent and capital estimates for Ondo state 1994: summary of approved budget - Ondo State Government (Nigeria); Ondo State Government, Nigeria (Akure : Ondo State Government, Nigeria, 1994)
This is the approved estimates and budget for capital and recurrent expenditure in Ondo State, Nigeria for 1994.
lje 15/3/2019
Arch.
Keywords: Budget; Expenditures, Public; Ondo State (Nigeria); Nigeria